Acute effect of isometric resistance exercise on blood pressure of normotensive healthy subjects - Silva, Carlos Alberto da (2013)
Cardiovascular diseases (CVD) are the main cause of morbidity and mortality in the general population [1]. Hypertension is awell established risk factor for the development of CVD, and its incidence increases with age [2]. Resistance exercise, dynamic [3,4] or isometric [5–7] have been used in the treatment of hypertension. However it is still not clear which is the impact of a session of isometric resistance exercise (IRE) in blood pressure (BP), i.e., its acute effect. According to Hagberg et al. [8], there is concern regarding that this type of exercise increases BP and is not a conditioning exercise, like the dynamic exercise, which is a conditioning exercise, and lowers resting BP and heart rate (HR). O'Hare and Murnaghan [9] pointed the risks of IRE in individuals with compromised cardiovascular function, including elderly people, or potentially compromised, such as left ventricule dysfunction, CVD, cardiomyopathy, aortic dilation and others, although IRE cronically decreases.